Shopping Centers as Elements of the Functional and Spatial Structures of Cities. Location, Impact, Change Tendencies, Development Perspectives - Agnieszka Rochmińska (Barometr Regionalny, 2017)
The appearance of large-surface complexes has led to the creation of new trade, service and entertainment centers in cities; these complexes have an impact on their surroundings. Due to the large scale of the phenomenon, it is important to determine the zones and nature of this influence, discuss the problem of the relationship between a shopping center and a city, and the tendencies and perspectives of development of shopping centers. A shopping center competes with its home city for the attractive urban and suburban areas and the dominating role, especially in terms of a trade, service and public space. On the other hand, it coexists with the city by releasing/regaining lands that have been degraded and contributes to improvements in transport. The development of shopping centers throughout the world occurs on a quantitative level — with varying dynamics, but still their number increases, and, importantly, on a qualitative level — since their new forms with altered offers emerge. Changes observed should be noteworthy to all Polish policy-makers when making well-thought-out decisions regarding locations. Local authorities need to realize that the permits they issue influence more than the changes in the functional and spatial structure of a city or commune.